Flow cytometric lyophilised reagent tube assay for peripheral blood neutrophil myeloperoxidase expression to rule out myelodysplastic neoplasms at a university hospital: a diagnostic accuracy study - Sophie Park; José Labarère; Arnaud Seigneurin; Lysiane Molina; Raymond Merle; Tatiana Raskovalova; Laura Scheffen; Marie-Christine Jacob; Simon Chevalier; Sylvie Tondeur; Bénédicte Bulabois; Mathieu Meunier; et al. (BMJ Open)
Objectives Although flow cytometric analysis of peripheral blood neutrophil myeloperoxidase expression can accurately rule out myelodysplastic neoplasms (MDS), it lacks reliability and efficiency due to the practical limitations of laboratory-developed liquid reagent-based assays. This study aimed to quantify the agreement and comparative discriminatory accuracy between a single-use flow cytometric lyophilised reagent tube (BD Lyotube Stain 468) and its laboratory-developed liquid reagent counterpart.Design Cross-sectional diagnostic accuracy study of two index tests against a reference diagnosis.Setting A university hospital in France.Participants Consecutive adult patients with an indication for bone marrow aspiration due to suspected MDS and unexplained peripheral blood cytopenia.Primary outcome MDS confirmed by cytomorphological evaluation of the bone marrow aspirate performed in duplicate by experienced haematopathologists blinded to the index test.Results Of 103 participants enrolled between July 2020 and August 2021, 37 had MDS (prevalence, 36%). The median intra-individual robust coefficient of variation (RCV) for myeloperoxidase expression was 30.9% using the BD Lyotube Stain 468 and 31.2% using the laboratory-developed liquid reagent assay, with an intraclass correlation coefficient of 0.94 (95% CI 0.91 to 0.96). The areas under the receiver operating characteristic curves were 0.83 (95% CI 0.74 to 0.90) and 0.82 (95% CI 0.73 to 0.89), respectively. Using a prespecified threshold of 30.0%, the corresponding sensitivity estimates were 89% (95% CI 75% to 97%) and 95% (95% CI 82% to 99%).Conclusion BD Lyotube Stain 468 performs as well as its laboratory-developed liquid reagent counterpart for the quantification of myeloperoxidase expression by peripheral blood neutrophils. It may obviate the need for invasive bone marrow aspiration in up to 40% of patients with suspected MDS.Trials registration number NCT04399018.